Hukum Progresif sebagai Solusi Kebebasan Berpendapat dengan Asas Demokrasi Pancasila - Laila, Khotbatul (University of Merdeka Malang, 2019)
Democracy guarantees the basic rights of every citizen to express their opinions freely. freedom that is limited by mechanism. Restrictions on freedom of opinion by mechanisms is so important to be implemented, in order to maintain the basic values of the Indonesian state as a constitutional democratic state. the law was formed to make people happy and give benefit to humans, not humans who are slaves to the law that tend to emphasize procedural justice. The application of progressive law towards the perpetrators of this law, is expected to be able to direct the law produced by the legislative process which tends to be elitist to lead to the interests of justice and the welfare of the people at large. Legislation is indeed one of the bridges to bring people to justice, but it is not the only one. The community realizes that law is a never final process. Regarding the series of laws relating to the mechanism of freedom of opinion, the application of progressive law is used as a means of harmonizing legal law between rigid written rules of law with a dynamic and always developing society.How to cite item:Â Laila, K. (2019). Hukum Progresif sebagai Solusi Kebebasan Berpendapat dengan Asas Demokrasi Pancasila.Â Jurnal Cakrawala Hukum, 10(2), 177-186. doi:https://doi.org/10.26905/idjch.v10i2.3546